Scoping Review of the Driving Behaviour of and Driver Training Programs for People on the Autism Spectrum. (28th August 2018) - Wilson, Nathan J.; Lee, Hoe C.; Vaz, Sharmila; Vindin, Priscilla; Cordier, Reinie
Abstract : Gaining a driver's licence represents increased independence and can lead to improved quality of life for individuals and their families. Learning to drive a motor vehicle and maintaining safe on-road skills are often more difficult for people on the autism spectrum. Many countries currently have no autism-specific licencing requirements for learner drivers, and there is a general lack of ASD-specific support and training packages for individuals, their families, and driving instructors. This review synthesises the peer-reviewed literature about the driving characteristics of drivers on the spectrum and driver training available for the cohort. The evidence in this review showed that individuals on the autism spectrum drive differently from their neurotypical counterparts. There are shortcomings in tactical skills of drivers on the autism spectrum, but the extent to which this affects their own safety or the safety of other road users is unclear. Tactical skills can be improved through training programs. There are few autism spectrum-specific learner training programs available. Development of an effective training program will benefit individuals on the spectrum to learn to drive, be independent, and be safe on the road.